2021
DOI: 10.7454/ijphn.v1i2.4761
|View full text |Cite
|
Sign up to set email alerts
|

Fulfilment of Minimum Acceptable Diet as Dominant Factor in Wasting in Children Aged 6–23 Months in Central Jakarta, Indonesia, 2019

Abstract: Wasting is a form of acute malnutrition characterized by significant and rapid weight loss resulting from inadequate food intake and infectious diseases. This study was to investigate the factors associated with wasting in children aged 6–23 months and the dominant factor among these. The study followed a cross-sectional study design. A total sample of 261 children was selected using multistage random sampling from 13 integrated healthcare centres in six administrative villages located in three sub-districts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…This could negatively affect the physical growth and neurodevelopment of IYC in Ghana. This is because it has been noted that IYC who do not meet MDD, MMF or MAD are at higher risk of malnutrition [36,37] which is significantly associated with neurodevelopment impairment [38].…”
Section: Plos Onementioning
confidence: 99%
“…This could negatively affect the physical growth and neurodevelopment of IYC in Ghana. This is because it has been noted that IYC who do not meet MDD, MMF or MAD are at higher risk of malnutrition [36,37] which is significantly associated with neurodevelopment impairment [38].…”
Section: Plos Onementioning
confidence: 99%
“…Although heredity is a factor that causes stunting, other studies have found that the dominant factor causing wasting is the fulfillment of a minimum acceptable diet. Based on a recent study conducted by Andina et al (2021) in Indonesia, the fulfillment of the minimum acceptable diet was found to be the dominant factor in wasting after controlling for education level, mother, and family income level. This study showed that supporting the family in providing adequate nutrition and care for their children is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Logit [P(Y=1)] = -0,429 -0,240 (X1) + 0,917 (X2) + 0,759 (X3)+ 0,459 (X4)+0,448 (X5)+0,173 (X6)+ 0,294 (X7)+ 1,104 (X8)-0,269 (X9)-0,353 (X10)-0,292 (X11)-0,473 (X12)+ 0,838 (X13)-0,435 Meskipun penelitian ini tidak menganalisis keterkaitan antara praktik pemberian makan pada anak usia 6-23 bulan dengan status gizi, namun dari beberapa penelitian yang telah dilakukan menunjukkan bahwa ketidaktercapaian praktik pemberian makan anak memiliki risiko yang tinggi untuk mengalami masalah gizi seperti stunting, wasting, dan underweight pada anak usia 6-23 bulan (Andina et al, 2021;Kimiywe & Chege, 2015;Limardi et al, 2020).…”
Section: Hasil Dan Pembahasanunclassified